(untitled) - Dowson, Andrew J (London, 2002)
This book is belong to Rapid Reference series. It provides the reader with authoritative and accessible information from a clinical expert in the field, to assist with treatment decisions. The book includes standard core content on migraine combined with the additional informationsuch as FAQs and patient organizationsneeded by the primary care practitioners to provide effective patient care. The books also include drug listings, clinical trials, information on future developments, and web site listings, to keep the reader up to speed with new developments and to extend their knowledge of migraine
Keywords: Migraine; Handbooks, manuals, etc